MERS-CoV Infection in a Pregnant Woman in Korea - Jeong, Soo Young (J Korean Med Sci, 2017)
Middle East respiratory syndrome (MERS) is a lethal respiratory disease — caused by MERS-coronavirus (MERS-CoV) which was first identified in 2012. Especially, pregnant women can be expected as highly vulnerable candidates for this viral infection. In May 2015, this virus was spread in Korea and a pregnant woman was confirmed with positive result of MERS-CoV polymerase chain reaction (PCR). Her condition was improved only with conservative treatment. After a full recovery of MERS, the patient manifested abrupt vaginal bleeding with rupture of membrane. Under an impression of placenta abruption, an emergent cesarean section was performed. Our team performed many laboratory tests related to MERS-CoV and all results were negative. We report the first case of MERS-CoV infection during pregnancy occurred outside of the Middle East. Also, this case showed relatively benign maternal course which resulted in full recovery with subsequent healthy full-term delivery without MERS-CoV transmission.